Transcriptomic profiling against Globodera pallida in resistant and susceptible potato roots - Carreño, Hans (2020)
Globodera pallida is a white potato cyst nematode present in the Andes, which causes huge losses to Peruvian farmers. An RNA-seq analysis allowed the identification of candidate genes that could mediate resistance against this pathogen. Two varieties, “María Huanca” (Solanum andigena) clone resistant (CIP 279142.12) and “Chimbina Colorada” (Solanum chaucha) (CIP 701013) clone susceptible to G. pallida, were used to identify differentially expressed genes. Total RNA from roots was extracted 72 hours post inoculation with second stage juveniles. Sequencing was done using the Illumina Hiseq 2500 platform. Reads were screened for quality issues and then mapped to the reference potato genome (clone DM1-3516 R44 v4.03). Here, we report 27717 and 27750 genes expressed in the resistant and susceptible variety respectively. The comparative analysis of expression identified 100 candidate genes. 91 genes were associated with resistance to G. pallida with Fold Change ≥ 2 (p <0.05). The remaining 9 R genes had Fold Change ≤ 1. We show differences in the expression of an NBS-LRR protein similar to Gro1-8, genes linked to late blight and TMV virus resistance.